Influence of the type of lightweight clay brick on the equivalent thermal transmittance of different types of facades on buildings - Morales, M P; Muñoz, Pedro; Juárez, M C; Mendivil, M A; Olasolo, P (Materiales de Construcción, 2017)
This paper compares the equivalent thermal transmittances of different façades built using commercial clay bricks with three different thicknesses and façades made using the same method but with ceramic bricks with optimized rhomboidal interior geometry. Equivalent thermal transmittances of 0.300 W/m2·K were recorded for the rhomboidal brick with a thickness of 0.290 m and a façade with thermo-acoustic insulation and a large format brick on the interior, but the final thickness of the façade was 0.445 m. For ventilated façades made of the proposed rhomboidal brick with thicknesses of 0.290 and 0.240 m an 8–9% improvement was found, with values of 0.312 W/m2·K and 0.339 W/m2·K, respectively. It can be concluded that in view of the small difference in thermal terms, the best option is to use a brick 0.240 m thick, as the overall thickness of the façade will not then exceed 0.300 m.
Influencia del tipo de bloque de arcilla aligerada en la transmitancia térmica equivalente de diferentes tipos de fachadas en edificios
En el presente trabajo se comparan las transmitancias térmicas equivalentes de diferentes fachadas ejecutadas con bloques comerciales de tres espesores 0,290 m, 0,240 m y 0,190 m, con el mismo montaje pero con un bloque cerámico optimizado con geometría interior romboidal. Se ha obtenido una transmitancia térmica equivalente de 0,300 W/m2·K para el ladrillo con geometría romboidal de 0,290 m de espesor y pared con aislamiento termoacústico y gran formato en el interior, con un espesor total de fachada de 0,445 m. Para fachadas ventiladas con el ladrillo romboidal propuesto con espesores de 0,290 y 0,240 m, se obtiene una mejora de un 8%–9%, con valores de 0,312 W/m2·K y 0,339 W/m2·K, respectivamente. Podemos concluir que, dada la pequeña diferencia en términos térmicos, la mejor opción es el uso de ladrillos de 0,240 m de espesor, siempre y cuando el espesor total de fachada no exceda los 0,300 m.
Keywords: ladrillo; cerámica; propiedades físicas; análisis térmico; método de los elementos finitos; brick; ceramic; physical properties; thermal analysis; finite element method; JCR; Scopus